Threads of peace : how Mahatma Gandhi and Martin Luther King Jr. changed the world - Krishnaswami, Uma, 1956- (Atheneum Books for Young Readers, 2021)
A dual biography and study of the lives of Mahatma Gandhi and Dr. Martin Luther King, Jr. Highlights these two men's nonviolent activism and how they preached peace and love for all people, regardless of nationality, race, or religion.